Asal-Usul dan Evolusi Aksara Suci Oṁ-Kāra di Bali Berdasarkan Data Prasasti Bali Kuno Abad VIII/IX - Rema I Nyoman; I Gusti Ngurah Sudiana; I Nyoman Suarka (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2024)
Various questions arise in the community, whether this OṀ-kāra is a product of Balinese culture or whether this script is a derivative of OM-kāra from India. This research raises the question of how is the origin and evolution of the OṀ-kāra script in Bali? This research data was collected through a literature study and supplemented by interviews. The results of this research are in the form of the history of the script that developed in Bali, namely Pre-Nagari and Ancient Bali including Bali Lumrah which was used to write down the origin and evolution of the sacred script OṀ-kāra in Bali. Based on the results of this study, it is known that this sacred script was derived through two scripts in Bali in the VIIIth/ IXth centuries, namely Pre-Nagari and Ancient Balinese, which were derivatives of the Brahmi script. However, this sacred script has not envolved after the VIIIth century in the pre-Nagari script. Instead, what is seen in its evolution is the sacred OṀ-kāra script written using the Balinese Lumrah script, which is a derivative of the Old Balinese script, from the niskala to the birth of creation theology.  Based on the evolution of this sacred script, it is known that OṀ-kāra is a sacred script as a symbol of God/ Ida Sang Hyang Widhi Wasa who niskala, then from the niskala, evolved into the nature of niskala-sakala, Nirguna-Saguna, Paramasiwa-Sadasiwa.